Feasibility of magnetic resonance-guided high-intensity focused ultrasound treatment targeting distinct nodular lesions in neurofibromatosis type 1. Issue 1 (18th August 2021) - Tydings, Caitlin; Yarmolenko, Pavel; Bornhorst, Miriam; Dombi, Eva; Myseros, John; Keating, Robert; Bost, James; Sharma, Karun; Kim, AeRang
Abstract: Background: Patients with Neurofibromatosis Type 1 (NF1) and plexiform neurofibromas (PN) often have radiographically diagnosed distinct nodular lesions (DNL) which can cause pain and weakness. Magnetic resonance-guided high intensity focused ultrasound (MR-HIFU) can precisely and accurately deliver heat to thermally ablate target tissue. The aim of this study is to evaluate whole-body MRIs from patients with NF1 and DNL, applying volumetrics and a consistent treatment planning approach to determine the feasibility of MR-HIFU ablation of DNL. Methods: A retrospective review of whole-body MRI scans from patients with NF1 and PN from CNH and NCI was performed. DNL are defined as lesions >3 cm, distinct from PN and lacking the "central dot" feature. Criteria for MR-HIFU thermal ablation include target location 1–8 cm from skin surface; >1 cm from visible plexus, spinal canal, bladder, bowel, physis; and ability to ablate ≥50% of lesion volume. Lesions in skull and vertebral body were excluded. Results: In 26 patients, 120 DNL were identified. The majority of DNL were located in an extremity (52.5%). Other sites included head/neck (7%), chest (13%), and abdomen/pelvis (28%). The predefined HIFU ablation criteria was not met for 47.5% of lesions ( n = 57). The main limitation was proximity to a vital structure or organ (79%). Complete and partial HIFU ablation was feasible for 25% and 27.5% of lesions, respectively. Conclusion: Based on imaging review of lesion location, technical considerations and ability to target lesions, thermal ablation with MR-HIFU may be a feasible noninvasive alternative for symptom management in patients with NF1 and symptomatic DNL.